2017
DOI: 10.5433/1679-0359.2017v38n4supl1p2775
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrated cassava co-product in starting piglets feeding

Abstract: Two experiments were carried out to determine the nutritional value of a dehydrated cassava co-product (DCC) and its effects on the performance and blood variables of piglets fed with different levels of DCC. In experiment I, a digestibility assay was performed and 30 whole-male crossbred piglets with initial body weight of 18.00 ± 0.673 kg were housed individually in metabolism cages and distributed in a completely randomized experimental design with 5 treatments, 6 replicates and one animal per experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…grain-rich diets tend to have better non-structural carbohydrate digestion in the small intestine and higher blood glucose supply, while fibre-rich diets promote higher conversion of structural carbohydrates in SCFA in the cecum and colon (López and Stumpf 2000). In recent researches by Castro et al (2017) and Leal (2018) using alternative ingredients similar to the present study in piglet feeding also observed no effect for the variable glucose.…”
Section: Growth Performance Plasma Parameters and Diarrhea Incidencesupporting
confidence: 64%
See 1 more Smart Citation
“…grain-rich diets tend to have better non-structural carbohydrate digestion in the small intestine and higher blood glucose supply, while fibre-rich diets promote higher conversion of structural carbohydrates in SCFA in the cecum and colon (López and Stumpf 2000). In recent researches by Castro et al (2017) and Leal (2018) using alternative ingredients similar to the present study in piglet feeding also observed no effect for the variable glucose.…”
Section: Growth Performance Plasma Parameters and Diarrhea Incidencesupporting
confidence: 64%
“…In similar researches, conducted by Castro et al (2017) and Leal (2018), who tested different levels of dehydrated cassava by-product and acerola industrial residue in piglet feeding, respectively. The authors reported an ADCGE of 73.74% to 84.99% and AMCGE of 71.80% to 84.67% for dehydrated cassava by-product, and an ADCGE of 28.21% and AMCGE of 27.84% for acerola industrial residue, finding a ME:DE ratio similar to obtained in the present study.…”
Section: Physicochemical-energetic Composition Coefficients Of Apparent Digestibility and Coefficients Of Apparent Metabolizability Valuementioning
confidence: 99%